Inovasi Visual Motif Ecoprint Teknik Blanket Untuk Bahan Pakaian - Marthaningrum, Idha Kusuma; Affanti, Tiwi Bina (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The background to this design is the lack of ecoprint pattern development using the blanket technique. In the market, most ecoprints with this technique come in the form of the same background color, although in fact it is still possible to develop patterns by utilizing the blanket application technique. So that new designs of ecoprint can be realized, engineered by the application of cloth blankets. The purpose of this design is to get a new visual pattern that is more varied than blanket technical textiles. as well as to satisfy the consumer tastes of ecoprint textile fans in particular. This design method uses the design approach Sp. Gustami explained that in the creation of craft works, it is carried out through three stages-six steps. The first stage of exploration which includes observation, and search for library sources. Second, the design stage, namely making several sketches, and making technical drawings. The third stage, embodiment, is the process of formation, and continued with the assessment and evaluation of the finished work” (Gustami, 2007:329). The result of this design is an ecoprint blanket fabric with a variety of different patterns from other blanket fabrics, with the result that several ecoprint fabric patterns have been engineered to apply blankets, namely in the form of 3 design ecoprint blankets which are included in the form of clothing textiles using natural dyes.